J18 Guided self-help for anxiety among people with Huntington's disease compared to treatment as usual: a randomised controlled feasibility trial (GUIDE-HD). (12th September 2022) - Dale, Maria; Eccles, Fiona; Melvin, Katie; Khan, Zaynah; Jones, Lee; Zarotti, Nicolò; Kiani, Reza; Simpson, Jane
Abstract : Background: Anxiety is one of the most common psychological difficulties reported among people with HD (pwHD) and has been shown to negatively impact on quality of life and everyday functioning. Expert guidelines recommend psychological therapy as the first treatment offered to people experiencing anxiety in early-stage HD. Guided self-help, an evidence-based psychological approach, is known to improve anxiety but has not yet been specifically applied to HD. Aims: GUIDE-HD aims to identify whether it is feasible to undertake a randomised controlled trial (RCT) to assess the use of guided self-help, aimed at improving anxiety among pwHD, compared to treatment as usual (TAU). Methods/Techniques: Participants will be at an early disease stage or pre-manifest HD. GUIDE-HD compares guided self-help with TAU and fifteen participants will be allocated to each group. Recruitment is ongoing in the UK. The 10-module intervention uses process-based cognitive behavioural therapy adapted to meet the specific needs of pwHD. Data gathered will assess whether the intervention and study design meet pre-determined feasibility criteria. HD participants and carers (where applicable) will be interviewed post-intervention and these data will be analysed qualitatively. Results: The study ends in Dec 2023. Thereafter, the results will be fully reported. Discussion: GUIDE-HD is a new psychological approach designed specifically to reduce anxiety among pwHD. This feasibility trial will help determine whether a fully powered RCT is warranted.